2009
DOI: 10.3233/jvr-2009-0451
|View full text |Cite
|
Sign up to set email alerts
|

Post-school outcomes of students with disabilities: A quantitative and qualitative analysis

Abstract: Post-school outcomes are measured by how successful students are integrating into their communities as productive citizens. Halpern's [10] "quality-of-life" transition outcomes were examined in this study using a mixed method research design of quantitative and qualitative measures. This study investigated a post-school outcomes survey administered in a southeastern state for the academic years 2003-2006 of former students who received special education services while in high school. The majority of the partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…Solutions have been proposed in various countries to improve transition planning (Curtis, Rabren, & Reilly, ; Davies et al., ; Geenen, Powers, & Sells, ; Rawson, ; Ward et al., ; Woodward, Swigonski, & Ciccarelli, ). In Quebec, there is a programme called “Transition from school to adult life” ( Transition de l'école à la vie active [ TÉVA ]), which is described as a set of coordinated, planned activities aimed at supporting students in achieving their goals after they leave school (free translation of definition in Office des personnes handicapées du Québec, , p. 40; Hamel & Dionne, ) to help youth with disabilities of all types to achieve a smooth transition.…”
Section: Introductionmentioning
confidence: 99%
“…Solutions have been proposed in various countries to improve transition planning (Curtis, Rabren, & Reilly, ; Davies et al., ; Geenen, Powers, & Sells, ; Rawson, ; Ward et al., ; Woodward, Swigonski, & Ciccarelli, ). In Quebec, there is a programme called “Transition from school to adult life” ( Transition de l'école à la vie active [ TÉVA ]), which is described as a set of coordinated, planned activities aimed at supporting students in achieving their goals after they leave school (free translation of definition in Office des personnes handicapées du Québec, , p. 40; Hamel & Dionne, ) to help youth with disabilities of all types to achieve a smooth transition.…”
Section: Introductionmentioning
confidence: 99%
“…Parents who participated in a Rural Special Education Quarterly focus group about transition planning indicated that nothing seemed to happen for their children unless they were willing to push and advocate for what they wanted. The parents pointed out that appropriate transition planning does not occur in a timely manner and that their children are not fully prepared for postsecondary life (Curtis, Rabren & Reilly, 2009). Strong support groups are critical for families when advocating for their students with disabilities, and strong family support and advocacy leads to more successful postsecondary outcomes (King et al, 2006).…”
mentioning
confidence: 99%
“…Until recently, students with ID/DD have not been afforded access to the benefits of college programs and environments Hart, Grigal, Sax, Martinez, & Will, 2006). Therefore, it is not surprising that students with disabilities are 4.5 times less likely to be enrolled in four-year universities, compared with their peers without disabilities (Curtis, Rabren, & Reilly, 2009;Newman, 2005). Sanford and colleagues (2011) recently reported that students with disabilities have lower participation rates in PSE than students without disabilities (i.e., 55% of students with disabilities opposed to 62% of their peers).Many colleges across the country are now broadening their mission to promote educational opportunities to an increasingly diverse population that includes individuals with ID/DD.…”
mentioning
confidence: 99%